Adrenal Cortical Neoplasm with Uncertain Malignant Potential Arising in the Heterotopic Adrenal Cortex in the Liver of a Patient with Beckwith-Wiedemann Syndrome - Eun Na Kim; Dong Eun Song; Hee Mang Yoon; Beom Hee Lee; Chong Jai Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2019)
Patients with Beckwith-Wiedemann syndrome (BWS) are predisposed to developing embryonal tumors, with hepatoblastoma being the most common type. Our patient showed hemihypertrophy, macroglossia, and paternal uniparental disomy in chromosome 11 and was diagnosed with BWS. When the patient was 9 months old, a 2.5×1.5 cm oval hypoechoic exophytic mass was detected in the inferior tip of his right liver. Preoperative imaging identified it as hepatoblastoma; however, histologic, immunohistochemistry, and electron microscopic findings were compatible with adrenal cortical neoplasm with uncertain malignant potential. The origin of the adrenal tissue seemed to be heterotopic. Here, we describe for the first time an adrenal cortical neoplasm with uncertain malignant potential arising in the heterotopic adrenal cortex located in the liver of a patient with BWS.